Nitrite Reductase and Biosensors Development (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2015)
Nitrite ions have emerged as one of the major problems in environmental and pollution issuesnowadays. Food products are the major source of these ions to preserve color. However, thereis a maximum permissible limit (MPL) for the use of nitrite in food. A lot of works in theliterature have been carried out on nitrite quantification and most of them are using simple andquick analysis methods. Recently, the advent of biosensor has allowed the fabrication ofsensors for the detection of nitrite. This paper specifically reviews the interest in the usage ofthe nitrite reductase enzyme as a biorecognition element for the application of nitritebiosensors.
Keywords: Nitrite, Biosensors, Nitrite reductase, Amperometric, Potentiometric